O(s) saber(es) e o(s) fazer(es) do professor formador :reflexões sobre a prática docente - Guedes, Neide Cavalcante (2006)
This study, developed in conjunction to the Pedagogical Practice research line and the Curriculum of Post-graduation in Education Program of UFRN is about investigations on formation of professors and teaching knowledge. Its objective is to analyze fundamental concepts for lecturing and the relationship that establishes between those concepts and the practice of forming professors. We adopted as referential the principles of social-historical approach, in the context of concepts making and development (Vygotsky, Luria and Rubinstein), and of collaborative theoric-methodological approach (Jacullo-Noto, Kemmis and Ibiapina). Collaboration with professors was mediated by diary writing, collaborative observation and conceptual network creation, essential to perceiving the given meanings to concepts that sustain the practice of 06 (six) forming professors from the UFPI Pedagogy Course. Teresina Campus. This way, reflections with collaborator professors allowed to build conceptual networks, in which prominence was given to the meanings of concepts that gave sustaining to their lecturing practices in the referred course, showing a fragmentation and disarticulation between theory and forming practice. They also indicate a need to give new concepts to the meanings of teaching concepts, learning and lecturing of these professors, in a meaning of a greater understanding about those concepts for their effective practice. On the context of collaborative reflection about conceptual networks, it was evident the conflict generated between the meanings attributed by professors and the practice developed in class, pointing to the need of rethinking the articulation between theory and practice not only on the formative process developed, but also on the continual formation of forming professors and on the construction of discussing spaces and materialization of the curricular principles of the Pedagogy Course